Contribution of macroalgal wrack consumers to dissolved inorganic nitrogen concentrations in intertidal pore waters of sandy beaches. (5th April 2019) - Lowman, Heili E.; Emery, Kyle A.; Kubler-Dudgeon, Lila; Dugan, Jenifer E.; Melack, John M.
Abstract: Sandy beaches are widespread ecosystems that often sustain food webs with allochthonous subsidies of organic matter. We examined the contribution of intertidal talitrid amphipods, a dominant consumer of macroalgal wrack subsidies on sandy beaches in temperate zones, to the remineralization of wrack and resulting nutrient concentrations in intertidal pore water. The abundance of wrack (as cover) is strongly correlated with that of talitrid populations in multi-year data from quantitative surveys (2013–2018). Ammonium (NH4 + ) is the dominant form of dissolved inorganic nitrogen at depths ranging from 0 to 160 cm in intertidal pore water collected in 2013, and pore waters are seldom hypoxic (dissolved oxygen < 2 mg L −1 ). We evaluated the effects of intertidal consumers on nutrient regeneration in laboratory mesocosms. Over the course of replicated 5-day incubations, treatments containing talitrid amphipods, Megalorchestia corniculata, and giant kelp, Macrocystis pyrifera, produced elevated dissolved concentrations of ammonium and nitrate, compared to treatments with only sand, seawater, and kelp. Our measurements suggest talitrid amphipods may elevate ammonium concentrations by 4–198 μM day −1 ; the ammonium produced may be utilized by beach microbes or exported offshore by tidal flushing. Our study highlights the role of intertidal consumers in maintaining important ecosystem functions, such as organic matter processing and nutrient regeneration. Highlights: Intertidal talitrid amphipod abundance is correlated with macrophyte wrack cover. Ammonium is the main species of dissolved inorganic nitrogen in beach pore water. Talitrid amphipods significantly contribute to pore water ammonium concentrations.